Não precisamos de régua, sim de Álgebra e compasso - Lugli, Ronaldo [UNESP] (2014)
This work was divided into two parts. The rst one presents how the geometric constructions are understood within the Algebra. This allows to see the impossibility, by using only ruler and compass, of trisecting certain angles and also of the duplication of a cube. The second part deals with some methods to perform constructions based on circular re ections and on the constructions of Mascheroni